VARIOUS ALTERNATIVES OF HYPOXIC TRAINING - Martin Pupiš; Pavol Pivovarniček; Zuzana Tonhauserová; Ratko Pavlović (Sport Scientific And Practical Aspects, 2025)
The aim of the paper was to compare the influence of three different alternatives of hypoxic training (a training in higher altitude – HA, an intermittent hypoxic training – IHT, and a hypoxic tent – HT). The research was executed on 10 athletes who all took part in higher altitude training and an intermittent hypoxic training. Four of the athletes from this sample took part in a training (a sleep) in a hypoxic tent. All the three alternatives lasted for approximately three weeks. In haematological indicators the number of erythrocytes, haemoglobin and hematocrit in HA and IHT increased from 3% to 4.9%. A more significant increase (25.3%, resp.26.2%) was measured in reticulocytes. In HT we measured the increase of reticulocytes in 17.9%; however in the remaining indicators we observed even smaller increase, namely 0.7 – 2.3%. From the point of spiroergometric indicators we observed the most significant increase in the VO2 max.kg -1 at ANT where we measured an increase of 8.7%, resp. 9.9%. Obviously, this indicator is directly influenced by the decrease of body weight, but also in absolute rate of VO2 max at ANT we measured an increase (7%, resp.7.7%), which indicates the increase of oxygen usability at ANT, thus the intensity corresponding to the competition load. In HT we also measured the increase in these parameters as well as a moderate decrease of body weight (0.3%), however only from 0.3 –1.5%. From the point of effectiveness we confirmed a positive influence of hypoxic training in all the three methods (HA, IHT, HT), but according to our findings the influence of HA and IHT was significantly higher than in HT.